2022
DOI: 10.3390/coatings12121815
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress in Functional Edible Food Packaging Based on Gelatin and Chitosan

Abstract: Nowadays, edible and eco-friendly packaging applications have been studied as an alternative to conventional/synthetic packaging due to the great interest of consumers in healthy, safe, and natural food, and of researchers in meeting the needs of consumers and producers. Various biopolymers are being extensively explored as potential materials for food packaging. The edible biopolymers utilized so far for packaging applications include proteins, lipids, and polysaccharides. Occasionally, these biopolymers have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 139 publications
(325 reference statements)
0
8
0
Order By: Relevance
“…Essential oils have good antimicrobial and antioxidant properties and can reduce lipid oxidation, improving the shelf life of foods [89]. Chitosan films supplemented with active agents have potential applications in meat preservation because of their antimicrobial properties.…”
Section: Lipid-based Packaging Materialsmentioning
confidence: 99%
“…Essential oils have good antimicrobial and antioxidant properties and can reduce lipid oxidation, improving the shelf life of foods [89]. Chitosan films supplemented with active agents have potential applications in meat preservation because of their antimicrobial properties.…”
Section: Lipid-based Packaging Materialsmentioning
confidence: 99%
“…It has been demonstrated that chitosan is nontoxic, biodegradable, biofunctional, and biocompatible, as well as having antibacterial properties. , Chitosan has the benefit of being able to contain useful elements like vitamins or minerals and has antibacterial activity when compared with other biobased food packaging materials. As a result, chitosan has been employed as a material for food packaging to preserve food quality. , …”
Section: Classification Of Marine Animal Derived Polysaccharidementioning
confidence: 99%
“…Gelatin can be used to obtain edible films [ 26 , 27 , 28 , 29 ] for meat products [ 30 , 31 ] or post-harvest fruit and vegetable [ 32 , 33 , 34 , 35 ] preservation. Mechanical properties such as fragility, rigidity, and brittleness are common in gelatin films, which often require the addition of other compounds to improve their performance such as chitosan [ 36 , 37 , 38 , 39 ], sodium alginate [ 40 ], grapefruit-seed extract and TiO 2 [ 41 ], starch [ 42 ], and plant extracts [ 43 , 44 ]. Whey is a water-soluble compound, with the highest proportion in the composition of milk, in which valuable proteins are dissolved, conferring it with an appreciable nutritional value.…”
Section: Introductionmentioning
confidence: 99%